Complex interactions between climate change, sanitation, and groundwater quality: a case study from Ramotswa, Botswana - McGill, B.M.; Altchenko, Yvan; Hamilton, S.K.; Kenabatho, P.K.; Sylvester, S.R.; Villholth, Karen G. (Springer, 2019)
Groundwater quantity and quality may be affected by climate change through intricate direct and indirect mechanisms. At the same time, population growth and rapid urbanization have made groundwater an increasingly important source of water for multiple uses around the world, including southern Africa. The present study investigates the coupled human and natural system (CHANS) linking climate, sanitation, and groundwater quality in Ramotswa, a rapidly growing peri-urban area in the semi-arid southeastern Botswana, which relies on the transboundary Ramotswa aquifer for water supply. Analysis of long-term rainfall records indicated that droughts like the one in 2013–2016 are increasing in likelihood in the area due to climate change. Key informant interviews showed that due to the drought, people increasingly used pit latrines rather than flush toilets. Nitrate, fecal coliforms, and caffeine analyses of Ramotswa groundwater revealed that human waste leaching from pit latrines is the likely source of nitrate pollution. The results in conjunction indicate critical indirect linkages between climate change, sanitation, groundwater quality, and water security in the area. Improved sanitation, groundwater protection and remediation, and local water treatment would enhance reliable access to water, de-couple the community from reliance on surface water and associated water shortage risks, and help prevent transboundary tension over the shared aquifer.